Analisa Kualitas Kompos Organik dengan Penambahan Bioaktivator Molase dan Bakteri Pemfiksasi N di Greenhouse Universitas Negeri Malang - Nurul Andini Setiawan; Agung Witjoro; Sitoresmi Prabaningtyas (Symbiotic: Journal of Biological Education and Science, 2024)
Waste is a problem faced by various sectors, especially the educational institution sector such as the State University of Malang. This problem can be overcome by composting organic waste such as leaves. The composting time ranges from 5-8 weeks, therefore it is necessary to add bioactivators to speed up the composting time. The research was conducted to analyze the quality of organic compost with the addition of bioactivator molasses and N-fixing bacteria (Bacillus paramycoides). This research was conducted in the Biology Department Laboratory, FMIPA UM, Green House, and in the BSIP Aneka Kacang laboratory for chemical content testing. The research used RAL with descriptive methods to analyze the research data. The treatments in this study were organic compost, water and no bioactivator (P0), organic compost, water and 1.3 ml molasses (P1), organic compost, water and 1.3 ml Bacillus paramycoides (P2), organic compost, water and 3.3 ml Bacillus pacarmycoides (P3), organic compost, water and 4.9 ml Bacillus paramycoides (P4). The results of the study based on physical and chemical analysis which includes, pH, temperature, aroma, texture, color, moisture content have met SNI 7763: 2018, but the results of the total macro nutrient content (N2+P2O5+K2O) of all treatments still do not meet SNI 7763: 2018 with a minimum content of 2%.